Cultural Perspectives of Corrupt Behaviour - Application of Trompenaars Model for Corruption - Réthi, Gábor (Theory, Methodology, Practice – Review of Business and Management, 2012)
This article examines the impact of cultural factors on corruption. It is always difficult to investigate this complex phenomenon. Moreover, we run into more questions and pitfalls when we would like to understand the influence of a multilateral phenomenon such as culture. I build on the work of Tsakumis et al. (2007) by conducting further empirical analysis of the relationship between cultural dimensions and corruption across countries using multiple measures of corruption to gain additional evidence on the subject (the impact of Trompenaarsian dimensions on corruption across countries). Based on data from 41 countries, and after controlling for economic development, the regression results indicate that the higher the level of collectivism the higher the level of diffusion, and that the lower the level of achievement, the higher is the level of tax evasion across countries. Managers should find the results of this study useful in assessing the likelihood of corruption from cultural perspectives, and in developing tax reform policies to reduce tax evasion and corruption.